Bipolar HiPIMS for tailoring ion energies in thin film deposition - Keraudy, Julien; Viloan, Rommel Paulo B.; Raadu, Michael A.; Brenning, Nils; Lundin, Daniel; Helmersson, Ulf (Surface & coatings technology, 2019)
The effects of a positive pulse following a high-power impulse magnetron sputtering (HiPIMS) pulse are studied using energy-resolved mass spectrometry. This includes exploring the influence of a 200 μs long positive voltage pulse (Urev = 10–150 V) following a typical HiPIMS pulse on the ion-energy distribution function (IEDF) of the various ions. We find that a portion of the Ti+ flux is affected and gains an energy which corresponds to the acceleration over the full potential Urev. The Ar+ IEDF on the other hand illustrates that a large fraction of the accelerated Ar+, gain energies corresponding to only a portion of Urev. The Ti+ IEDFs are consistent with the assumption that practically all the Ti+, that are accelerated during the reverse pulse, originates from a region adjacent to the target, in which the potential is uniformly increased with the applied potential Urev, while much of the Ar+ originates from a region further away from the target over which the potential drops from Urev to a lower potential consistent with the plasma potential achieved without the application of Urev. The deposition rate is only slightly affected and decreases with Urev, reaching ~90% at Urev = 150 V. Both the Ti+ IEDF and the small deposition rate change indicate that the potential increase in the region close to the target is uniform and essentially free of electric fields, with the consequence that the motion of ions inside the region is not much influenced by the application of Urev. In this situation, Ti+ will flow towards the outer boundary of the target-adjacent region, with the momentum gained during the HiPIMS discharge pulse, independently of whether the positive pulse is applied or not. The metal ions that cross the boundary in the direction towards the substrate, and do this during the positive pulse, all gain an energy corresponding to the full positive applied potential Urev.